Sliding mode control of uncertain parameter-switching hybrid systems - Wu, Ligang; Shi, Peng; Su, Xiaojie (Wiley series in dynamics and control of electromechanical systems, 2014)
"Presents new, state-of-the-art sliding mode control (SMC) methodologies for uncertain parameter-switching hybrid systemsSliding Mode Control of Uncertain Parameter-Switching Hybrid Systems presentsnew, state-of-the-art sliding mode control (SMC) methodologies for uncertain parameter-switching hybrid systems (including Markovian jump systems, switched hybrid systems, singular systems, stochastic systems and time-delay systems).The first part of this book establishes a unified framework for SMC of Markovian jump singular systems and proposes new SMC methodologies based on the analysis results. In the second part, the problem of SMC of switched state-delayed hybrid systems is investigated, and finally the parallel theories and techniques that have been developed are extended to deal with switched stochastic hybrid systems.Solved problems with new approaches for analysis and synthesis of continuous- and discrete-time switched hybrid systems, (including stability analysis and stabilization, dynamic output feedback control,) are also included throughout. Presents new, state-of-the-art sliding mode control (SMC) methodologies for uncertain parameter-switching hybrid systems Provides a unified, systematic framework for handling SMC problems Introduces new concepts, models and techniques Includes solved problems throughout "..